Joseph Sugar Baly: The man and his entomological works. - Staines, Charles L.; Staines, Susan L. (Contributions to Entomology = Beiträge zur Entomologie, 1999)
Joseph Sugar Baly (1816-1890) was an English medical doctor who became a world authority on the Chrysomelidae (Coleoptera). From 1855 until 1891 he published 102 papers in which he described 217 genera, 2 subgenera, and 2.219 species. This article presents a brief biographical sketch, a bibliography of his entomological works, and a list of proposed taxa.KeywordsBaly, biography, bibliography, proposed taxa.